Автобиографическое начало в романе Захара Прилепина Патологии - Osiewicz, Bartosz (Acta Polono-Ruthenica, 2019)
This article is devoted to the analysis of the autobiographical element in the novel by Zachar Prilepin The Pathologies. It can be noticed that the contemporary Russian writer resigns from postmodernism poetics and turns to the tradition of realistic literature. What is more, he wants to overcome the crisis of authorship. The novel The Pathologies is also a response to the esthetic need of modern readers, who are interested in broadly understood autobiography and observation of life in all its dimensions. Prilepin – a veteran of The First and the Second Chechen Wars – shares his soldier’s experience and emotions. The autobiographical element is present in The Pathologies on various levels (hero, narration, extreme situation).